Acute cor pulmonale from saddle pulmonary embolism in a patient with previous COVID-19: should we prolong prophylactic anticoagulation? (2020)
Severe coronavirus disease 2019 (COVID-19) is known to be associated with a heightened risk of thromboembolism. However, the risk associated with mild and moderate illness from COVID-19 is unknown, and there is no current recommendation for prophylaxis againstthromboembolism in patients after hospital treatment, unless there are established thrombophilic risk factors. We report the case of a 52-year-old woman who presented with massive saddle pulmonary embolism 1 week after initial hospital discharge, which was treated successfully with thrombolysis. This case raises the question of whether extended prophylactic anticoagulation should be considered even in low-risk COVID-19 cases